Path to success: female leaders in German neurosurgery - Weiß, Miriam; Dogan, Rabia; Eisenberg, Ulrike; Velalakan, Aruni; Krüger, Jutta; Moritz, Ina; Nistor-Gallo, Dorothea; Flueh, Charlotte; Janz, Claudia; Ahmadi, Rezvan; Hakvoort, Karlijn; Forster, Marie-Thérèse (Neurosurgical review, 2023)
Despite advances in gender equality, only 6% of German neurosurgical departments are currently led by women. With regard to their pioneering work and the importance of their role model effect, we aimed at reporting on the career pathways of the present and former female chairs of neurosurgical departments in Germany. We approached current and former female chairs in German neurosurgery and gathered descriptive information on their ways into leadership positions through structured interviews. Data were obtained from 16/22 (72.7%) female neurosurgical chairs, aged between 44 and 82 years. They completed their training within 6.5 ± 0.6 years, and it took them further 14.5 ± 5.9 years between training completion and chair acquisition. Having obtained their chair positions between 1993 and 2020, six (37.5%) of them have retired or changed career tracks. Of ten (62.5%) chairs still practicing, two are directors of university departments. Twelve (75.0%) hold professorships. Nine chairs (56.3%) are married, eight (50.0%) having children. Five chairs reported having experienced gender-based discrimination. Twelve had a male mentor or role model, two had a female role model, while only one had a female mentor. This study characterizes the to date small number of female neurosurgical chairs in Germany and their paths to neurosurgical leadership positions. In future, these should become historical in order to perceive the presence of women in leadership positions as self-evident normality, reflecting our society. However, further analyses comparing paths of both female and male neurosurgical chairs are necessary to explore gender-based differences in achieving neurosurgical leadership positions.
Gesehen am 19.01.2024